Gamiefects: um framework de apoio na avaliação de gamificação para contextos educacionais - Reinheimer, Wendel Souto (2022)
In recent years, gamification has become an emerging phenomenon being applied in several fields of human activity. In the educational environment, gamification has been used as a promising strategy in order to promote learning, motivation and student engagement. However, some studies have shown that its use does not always bring positive results, making it essential to consider the evaluation process an important aspect, since this procedure allows verifying the effectiveness of gamification and whether the objectives of gamification are being achieved. In this context, there was a scarcity of specific evaluative methods or approaches for gamification, resulting in the lack of instructions and guidelines for carrying out this procedure. Given this scenario, based on a methodology for the elaboration of scientific research in information systems, the DSRM (Design Science Research Methodology), this dissertation presented THE GAMIEFECTS, a structure composed of five dimensions that aims to support the evaluation of gamified environments for educational contexts. GAMIEFECTS was inspired by the DECIDE Framework and presents five conceptual dimensions that address specific contents of the gamification literature. The first Dimension of the framework deals with aspects that involve defining the objectives of an evaluation. Dimension 2 brings recommendations related to the analysis of the context and the moment of evaluation. Dimension 3 demonstrates forms of evaluation and some validated instruments found in the literature. Dimension 4 addresses ethical aspects when the evaluation involves users and finally, Dimension 5 discusses some recommendations on the presentation of results. GAMIEFECTS was validated through a case study in the gamified Duoling environment in order to validate all the dimensions proposed in the framework. To this end, a descriptive exploratory study was designed, covering all types of evaluation techniques dealt with in the Framework. The first validation contemplated the empirical evaluation techniques, for this, a simulation was developed in which the data used were generated from an auxiliary tool for data generation. The second part of the study included the development of a questionnaire to evaluate the gamification design from Duolingo game elements and finally, the last stage of the case study involved the application of a heuristic evaluation on the Duolingo platform. The results found suggest that GAMIEFECTS is capable of assisting in processes that involve the planning, execution and presentation of results in a gamification assessment for educational contexts. Despite this, through this study, one can see the need to apply the framework in real usage scenarios as in a longitudinal study, as well as a validation from a panel of gamification experts so that the framework can be measured in terms of usability, flexibility, adaptability and other quality criteria relevant to its structure.